Knowledge sharing process in a contemporary Mangyan swidenning community - David, Myra E.; Cardenas, Virginia R.; Cruz, Federico A.; Talatayod, Elvira S.; Pulhin, Juan M. (2012)
The paper elucidates the application of indigenous ecological knowledge and knowledge sharing processes, i.e., socialization (informal education) and externalization (formal and nonformal or extension education), in the understanding...
Keywords: Mangyans; Mangyans -- Formal education